(untitled) (Bangladesh Journal of Plant Taxonomy, 2015)
The study revealed the occurrence of 528 species of vascular plants belonging to 356 genera and 111 families in the Sundarban Mangrove Forest of Bangladesh. Among these species, 24 were pteridophytes and the rest were angiosperms, of which only 24 were true mangroves and 70 were mangrove associates. Magnoliopsida and Liliopsida were represented by 373 and 131 species, respectively. These species belonged to 345 herbs, 89 shrubs and 94 trees. Sixty-four species were climbers, 14 were epiphytes, 6 were parasites, and 7 were palms. The species number per family varied from 1 to 42. In pteridophytes, Pteridaceae with 4 genera and 5 species was the largest family. In angiosperms, Fabaceae with 24 genera and 42 species and Poaceae with 27 genera and 42 species were the largest families, respectively, in Magnoliopsida and Liliopsida. Most of the species included in this checklist were found in oligohaline zone, Sarankhola range and the forest margins, and recognized as economically important. Eleven species categorized as threatened in Bangladesh were found to occur in this mangrove forest. Bangladesh J. Plant Taxon. 22(1): 1741, 2015 (June)